Rekonstruksi Tata Kelola Pertambangan melalui Maqasid al-Sharia: Menuju Pengelolaan Sumber Daya Alam yang Berorientasi pada Kesejahteraan Publik - Nasrullah, Nasrullah; Muhjad, Hadin; Erlina, Erlina; Abdullah, Dadang (Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study analyzes the governance of mining resources in Indonesia through the lens of Maqasid al-Sharia as a normative foundation to reconstruct coal mining licensing systems toward a welfare-oriented model. The current framework, despite legislative reforms under Law No. 4 of 2009 and Law No. 3 of 2020, continues to grapple with environmental degradation, regulatory fragmentation, and unequal resource distribution. Using a normative legal research method, the research examines statutory regulations, Islamic legal doctrines, and principles of maslahah (public benefit), ‘adl (justice), and hifz al-mal (protection of wealth) within the context of Article 33 of the 1945 Constitution. The historical evolution of mining regulation, from colonial concessions to the centralized IUPK system, reveals a persistent tension between economic exploitation and public welfare. This study proposes a reconstruction of mining governance that integrates Islamic legal objectives to ensure justice, environmental protection, and inclusive development. By embedding Maqasid al-Sharia within the legal framework, mining governance can be redirected toward the public good and sustainable state stewardship.